The Effects of Processing Methods on the Quality of Arabica Kintamani Green Beans - I Gede Pasek Mangku; Luh Suriati; Dewa Gede Yudi Ardana; Wayan Widiantara Putra (International Journal of Food Studies)
The coffee of Arabica Kintamani is one of the most popular coffees in the world due to its specific taste. The quality of coffee beans depends on the post-harvest and processing method. Dry processing and wet processing are the most popular methods used and each process produces different quality coffee beans. The objective of this research was to study and analyze various processing methods of coffee beans and to determine the best processing method to apply by the farmers and processors. This research consisted of three processing methods for the coffee namely dried processing (natural); wet processing; and semi-wet processing (honey). The research used a randomized complete design with one factor and five replications. The study showed that dry processing (natural) produced good quality coffee beans compared with wet or semi-wet processing, with significantly higher polyphenols content of 40.80 ± 0.053 mg GAE g−1 , approximately the same caffeine content (1.19 ± 0.016 %), significantly higher antioxidant activity (% DPPH) 89.53 ± 0.229 % with an EC50 equal to 102.44 ± 0.130 mg L−1 , similar lightness 13.63 ± 8.281 and a significantly lower moisture content of 7.54 ± 0.474 %. This indicated that dry processing could be used as an alternative processing method by farmers and processors due to it being easier, cheaper, with more efficient water use as well as giving a product contained the highest levels of polyphenols and antioxidant activity that are good for human health.